Factors Related to Nurse Respond Time on Handling of Emergency Patient in IGD Room at Sawerigading Hospital - Sriwahyuni Sriwahyuni (Journal of Health Science and Prevention, 2019)
The services of emergency patients play a very important role based on the principle of â€™time saving is life savingâ€™. This means that all actions taken during an emergency condition must be truly effective and efficient. This is reminiscent of the condition that people can lose their lives just in minutes. Response time depends on the speed available as well as the quality of providing assistance to save lives/prevent disability. There are many factors that influence nurses' response time which are education level, knowledge, length of work, and training. To know factors related to nurse-responded time on handling of emergency patient in IGD Room at Sawerigading Hospital. The research design used was cross-sectional analytic correlation. The respondents were all nurses implementing in IGD Room at Sawerigading Hospital. The population is this study were 31 nurses in IGD Room at Sawerigading Hospital and were selected using total sampling method. . Data analysis used chi-square test. There is a long working relationship with nurse respond time on emergency patient handling (value Ï = 0,014 <Î± = 0,05). There is norelationship of education with nurse time responder (value Ï = 0,729> Î± = 0,05). There is no relationship of gadar training with nurse respond time (value Ï = 0,307> Î± = 0,05). Factors related to nurse respond time on handling of emergency patient in IGD Room at Sawerigading Hospital that is long work. Therefore, the quality of service in the ER should also be improved through improvement efforts concerning with resources, facilities, procedures, services, and other technical aspects.